Comparative Assessment of Feed-forward Schemes with NCTF for Sway and Trajectory Control of a DPTOC - Mohd Ashraf, Ahmad; Raja Mohd Taufika, Raja Ismail; Mohd Syakirin, Ramli (2010)

(untitled)
This paper presents a comparative assessment of feed-forward schemes in hybrid control schemes for anti-swaying and trajectory tracking of a double-pendulum-type overhead crane (DPTOC) system. A nonlinear DPTOC system is considered and the dynamic model of the system is derived using the Euler-Lagrange formulation. To study the effectiveness of the controllers, initially nominal characteristics following trajectory following (NCTF) is developed for position control of cart movement. The controller design, which is comprised of a nominal characteristic trajectory (NCT) and PI compensator, is used to make the cart motion follow the NCT. This is then extended to incorporate feed-forward schemes for anti-swaying control of the system. Feed-forward control schemes based on input shaper and filtering techniques are to be examined. The input shaper and filtering techniques with different orders were designed based on properties of the system. The results of the response with the controllers are presented in time and frequency domains. The performances of hybrid control schemes are examined in terms of level of input tracking capability, sway angle reduction and time response specifications in comparison to NCTF controller. Finally, a comparative assessment of the control techniques is discussed and presented.